Designing a brief behaviour change intervention to reduce sexually transmitted infections: a discrete choice experiment. (August 2018) - Miners, Alec; Llewellyn, Carrie; King, Carina; Pollard, Alex; Roy, Anupama; Gilson, Richard; Rodger, Alison; Burns, Fiona; Shahmanesh, Maryam
To understand whether people attending sexual health (SH) clinics are willing to participate in a brief behavioural change intervention (BBCI) to reduce the likelihood of future sexually transmitted infections (STIs) and to understand their preferences for different service designs, we conducted a discrete choice experiment (DCE) with young heterosexual adults (aged 16–25 years), and men who have sex with men (MSM) aged 16 or above, attending SH clinics in England. Data from 368 participants showed that people particularly valued BBCIs that involved talking (OR 1.45; 95%CI 1.35, 1.57 compared with an 'email or text'-based BBCIs), preferably with a health care professional rather than a peer. Findings also showed that 26% of respondents preferred 'email/texts' to all other options; the remaining 14% preferred not to participate in any of the offered BBCIs. These results suggest that most people attending SH clinics in England are likely to participate in a BBCI if offered, but the type/format of the BBCI is likely to be the single important determinant of uptake rather than characteristics such as the length and the number of sessions. Moreover, participants generally favoured 'talking'-based options rather than digital alternatives, which are likely to require the most resources to implement.